THE EFFECT OF ACUPRESSURE WRISTBAND ON NAUSEA VOMITING IN BREAST CANCER PATIENTS WHO RECEIVED CHEMOTHERAPY - Endah Panca Fatma (Department of Nursing, Faculty of Health Sciencce, Universitas Brawijaya, 2018)
Chemotherapy is one of the therapies for cancer patients that cause some side effects, one of them is nausea and vomiting. Nausea and vomiting are still felt by patients even though they take antiemetics. Nausea dan vomiting can cause fluid and electrolyte imbalance. The aim of this study was to analysis the effect of combination acupressure wristband and antiemetic among chemotherapy induced nausea vomiting (CINV) on breast cancer patients. This research used quasi experimental research method, with a pre-post test with the control group. The sampling techniques was consecutive sampling with 25 respondents both in intervention group and control group. In the intervention group had received an acupressure wristband. CINV measured on the second day until fourth day after chemotherapy. Nausea and vomiting score were measured twice a day by a telemonitoring methode by Rhodes Index Nausea, Vomiting and Retching (INVR) questionaire. Data were analyzed by paired t-test, independent t-test, Wilcoxon test and Mann Whitney. The result of this study showed that acupressure wristband significantly reduce the chemotherapy induced nausea and vomit (p value = 0.000). The use of acupressure wristband combined with antiemetic therapy can significantly decreaseÂ chemotherapy induced nausea and vomiting in breast cancer patients. Acupressure wristband recommended for consideration nursing intervention in treating breast cancer patients who experience nausea and vomiting.